Development and testing of a 25-item patient satisfaction scale for Black South African diabetic outpatients - M.S. Westaway; P. Rheeder; D.G. van Zyl; J.R. Seager (AOSIS, 2002)
Although there is general agreement that patient satisfaction is an integral component of service quality, there is a paucity of South African research on reliable and valid satisfaction measures and the effects of health status on satisfaction. A 25-item patient satisfaction scale was developed and tested for evaluating the quality of health care for black diabetic outpatients. It was hypothesised that: (1) the underlying dimensions of patient satisfaction were interpersonal and organisational; and (2) patients in poor health would be less satisfied with the quality of their care than patients in good health. The questionnaire was administered to 263 black outpatients from Pretoria Academic Hospital and Kalafong Hospital. Factor analysis was conducted on the patient satisfaction scale and three factors, accounting for 71 % of the variance, were extracted.